PERUBAHAN KERUSAKAN LAHAN PULAU MADURA MENGGUNAKAN DATA PENGINDERAAN JAUH DAN SIG - Nanik Suryo Haryani; - Kustiyo; Rokhis Khomarudin; - Parwati (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2006)
Development activities that do not pay enough attention to the evironmental aspect will bring about the effect to the evironment, particularly to the event of land damage. The effort to control and recover the land damage calls for the complete abd the accurate data and information. Along with the remote sensing technology development, it enables to study the land damage effectively and efficiently in the large scale region. The method used in the research is by utilizing the Landsat-TM image and the Geographic Information System (GIS) to determine the stage of land damage.The potential determination of land damage is carried out by weighting the indicator of land damage that all together function as the variable. The output obtained shows that the stage of land damage in Madura Island from 1994 until 2001 is the condition or the stage of land damage that belongs to the rather damaged class decreases to 0.90%, while the stage that belong to the damaged class is 3.90% and the stage of the big damaged is 0.14%.